Rancang Bangun Alat Monitoring Keadaan Air Danau Berbasis Arduino Terintegrasi Web di Limnologi LIPI - Daniel Jose Andre; Endra Triwisesa; Ridwan Siskandar (PUSAT SAINS INDONESIA, 2020)
Lake is an inland water ecosystem whose existence is very important for human life (Lihawa & Mahmud, 2017). For humans, the importance of lakes means much more than their area. The existence of a lake ecosystem provides beneficial functions for human life (Pratama et al., 2018). Apart from being a source of raw water, irrigation and hydroelectric power, inland public waters have high economic benefits, especially in the development of the fisheries sector, both capture and cultivation. The potential for capture fisheries in mainland public waters is estimated at 3 million tonnes (Triharyuni et al., 2014). The multisectoral utilization and activities in the area around the lake have caused the lake ecosystem to experience increasingly severe degradation until now.To detect and measure the effect of a pollutant on environmental quality and to determine the improvement in environmental quality after the pollutant has been removed (Bahri, 2018). Based on several studies that have been carried out in relation to water quality, parameters that are quite influential on the development of cultivated fish include temperature, salinity, brightness, turbidity, degree of acidity (pH) and dissolved oxygen (Mahabror 2013).